2012
DOI: 10.1111/j.1472-765x.2012.03312.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and antagonistic properties ofStreptomycesstrains isolated from Saharan soils, and evaluation of their ability to control seedling blight of barley caused byFusarium culmorum

Abstract: During a screening for potential plant disease control actinomycetes, a total of 133 strains were isolated from Saharan soil samples of seven Algerian regions by dilution technique on chitin-vitamins agar medium. Screening for antagonistic properties using streak assay method showed that 25% of isolates demonstrated strong activities against a wide range of plant pathogenic fungi. Due to their strong anti-Fusarium activities, six of these isolates were selected and subsequently related to Streptomyces species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…In fact, after treatment with IA1 or YA, the percentage of plants affected by chocolate spot or Fusarium wilt was considerably reduced. These results agree with previous investigations on Saharan Streptomyces strains, which have already demonstrated their potential usefulness as biocontrol agents . Shimizu et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, after treatment with IA1 or YA, the percentage of plants affected by chocolate spot or Fusarium wilt was considerably reduced. These results agree with previous investigations on Saharan Streptomyces strains, which have already demonstrated their potential usefulness as biocontrol agents . Shimizu et al .…”
Section: Discussionsupporting
confidence: 93%
“…In fact, after treatment with IA1 or YA, the percentage of plants affected by chocolate spot or Fusarium wilt was considerably reduced. These results agree with previous investigations on Saharan Streptomyces strains, which have already demonstrated their potential usefulness as biocontrol agents [16,17]. Shimizu et al [12] highlighted the establishment of an induced disease resistance on Rhododendron seedlings after treatment with an Act-D producing strain, Streptomyces R-5, and also showed its strong suppressive impact on the fungus Pestalotiopsis sydowian, the causal agent of Pestalotia disease in the rhododendron.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies revealed only the antagonist effects of Streptomyces strains against toxin producing fungi (Yekkour et al, 2012). According to Verheecke et al (2014), Streptomyces strains inhibited AFB1 production in A. flavus by gene repression.…”
Section: Discussionmentioning
confidence: 99%
“…Several successful experiments have been conducted with them about their antagonist effects on mycotoxin producing fungi. Some Streptomyces strains extracted from the Saharan soil were detected to reduce disease symptoms on barley seedlings caused by Fusarium culmosum (Yekkour et al, 2012). Streptomyces (MRI142) strain produced the aflastatin A, which prevented effectively the biosynthesis of aflatoxin produced by Aspergillus parasiticus (Sakuda et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported satisfactory results in use of Streptomycetes against some pathogens. (Kamel et al 1993;Yan-Min et al 2000;Hoster et al 2005;Yekkour et al 2012). In the present research, 70 isolates of Streptomycetes were taken from citrus grove soils of Kerman province, Iran, and screened against several phytopathogenic fungi.…”
Section: Introductionmentioning
confidence: 92%